Evaluation of hexagonal boron nitride as a new tablet lubricant - (:unkn) unknown (My University, 2005)
In this study, hexagonal boron nitride (HBN) was evaluated as a new lubricant for pharmaceutical tablet manufacturing. The other conventional lubricants such as magnesium stearate (MGST), stearic acid (STAG), and glyceryl behenate (COMP) were also tested along with HBN. Tablets were manufactured on an instrumented single-station tablet press to monitor and quantify the lower punch ejection force (LPEF). The force ratio, tablet crushing strength, disintegration time, and thickness were measured. The lubricant film formation and lubricant distribution in tablets were studied using the scanning electron microscopy (SEM) and electron probe micro analyzer (EPMA). Based on the force ratio, a good lubrication was obtained at 1% for MGST and HBN; in contrast, STAG and COMP did not show a good lubrication. After 1%, all lubricants performed well. MGST was found to be the most effective lubricant based on LPEF-lubricant concentration profile. HBN provided a 50% decrease in LPEF at 2% lubricant concentration and was rated as an effective tablet lubricant. HBN was better than either STAC or COMP. Unlike MGST, HBN had no significant prolongation effect on tablet disintegration times. Copyright © 2005 Taylor & Francis Inc.
Keywords: Force ratio; Hexagonal boron nitride; Lower punch ejection force (LPEF); Lubricants; Tablets